2021
DOI: 10.1038/s41598-021-87255-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic and morphological relationships among the botryllid ascidians (Subphylum Tunicata, Class Ascidiacea, Family Styelidae)

Abstract: Ascidians (Phylum Chordata, Class Ascidiacea) are a large group of invertebrates which occupy a central role in the ecology of marine benthic communities. Many ascidian species have become successfully introduced around the world via anthropogenic vectors. The botryllid ascidians (Order Stolidobranchia, Family Styelidae) are a group of 53 colonial species, several of which are widespread throughout temperate or tropical and subtropical waters. However, the systematics and biology of this group of ascidians is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 69 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…In this study, we selected the mitochondrial cytochrome c oxidase subunit 1 (COI) for the detection of one-and two-toned color B. diegensis in South Korea. The COI was identified as the marker of choice for species discrimination [28] and has been effectively used for detecting NIS [8,29] and botryllids [27,30]. As a result, we recognized the presence of B. diegensis in South Korea based on DNA barcoding analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we selected the mitochondrial cytochrome c oxidase subunit 1 (COI) for the detection of one-and two-toned color B. diegensis in South Korea. The COI was identified as the marker of choice for species discrimination [28] and has been effectively used for detecting NIS [8,29] and botryllids [27,30]. As a result, we recognized the presence of B. diegensis in South Korea based on DNA barcoding analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several widely distributed botryllids, including B. diegensis, have been misidentified, and the correct identification of these species is critical for understanding their biology and spread, as well as for detecting the spread of additional species [27]. Preliminary molecular analyses revealed that these one-toned color colonies included specimens attributable to B. diegensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…i.e., many species regenerate the whole body via asexual budding or upon extensive injury, others have more restrained regenerative potential (Alié et al, 2020;Nydam et al, 2021). Tunicates of the group of Botryllinae and in particular Botryllus schlosseri have been used for several decades as experimental laboratory models (Manni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…If WBR is truly absent in B. schlosseri , as our study suggests, and in S. brakenhielmi (which is simply a speculation), that reduces the taxonomic breadth of WBR. The remaining species documented to have vascular budding, with currently well-resolved phylogenetic positions, all fall within a single clade, notably to the exclusion of B. schlosseri [ 45 , 46 ]. Thus, if the third hypothesis is correct, vascular budding and WBR evolved once within one clade of the Botryllinae and appear to be predominantly linked to coping with environmental adversity—either for survival after major injury or as a mechanism to allow for colony dormancy and future recovery.…”
Section: Discussionmentioning
confidence: 99%